Service charge-based benefit function in the multi microgrids by creating optimal coalition and employing demand response programs - Ramin Pouyan; Mohammad Tolou Askari; Meysam Amirahmadi; Vahid Ghods (Unconventional Resources)
By appearing and introducing restructured power system concept, traditional vertical power system is converted to the locally generation units or the collection of generation units, storage units and loads as microgrid (MG). To better power supplying and eliminating the requisition to the installing new power plant, utilizing multi-MG is the best choice. This aim needs to use the electrical infrastructure of distribution network (DN). To make it feasible and economical, MG operators should pay costs to utilizing DN operator's (DNO)electrical infrastructure. This cost is introduced as service charge. In this work, the main function is defined as total benefits of MGs. In the benefit function, service charge costs are considered. To increase the total benefits of MGs and supply loads energy demands, creating coalition among MGs is considered. Furthermore, to increase the total benefits of MGs and DNO demand response programs (DR) are employed. Shapely value method is used to solve benefit function. In case without coalition among MGs, and with employing DR programs, in the residential-based DR programs, MGs total benefits increase 12 %, complex building base load MGs total benefits increase 24 % and industrial-based MG's benefits increase 18 %. In the case with creating coalition, these values are changed to 27 %, 38 % and 23 %, respectively.